A Conceptual Model for Integration of Indian Food Supply Chains. (August 2016) - Parwez, Sazzad
This article is an attempt to explore the problems faced by Indian agriculture for food security in terms of inadequate infrastructure and highly inefficient supply chain. Due to lack of efficient infrastructure, supply chain mechanism and food processing, around 30–35 per cent of all foods produced in India are wasted. This article examines the critical issues at subsystem of agriculture supply chain, with a view to integrating them in efficient and effective manner. This article broadly covers some important aspects of agriculture supply chain in India—identification of issues at different levels in the supply chain; transformation in the agriculture due to various supply chain interventions; and the role of information technology in supply chain management. As this article is based on both primary and secondary research methodology, it has led us to finding that there is not much research in this field in India and importance of integration in agricultural development. The article concludes that efficient supply chain plays a very important role for development and is a contemporary issue for agriculture, therefore, the government and the corporates must address the issue of integration, infrastructure development and information management to achieve the objective of a feasible agricultural sector which will lead to food security for all.